2010
DOI: 10.1007/s11605-009-1131-0
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Complications Secondary to Post-Cholecystectomy Clip Migration: A Review of 69 Cases

Abstract: PCCM can occur at any time but typically occur at a median of 2 years after cholecystectomy. Clinical presentations are similar to those with primary or secondary choledocholithiasis. Most can be managed successfully with ERCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
145
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(149 citation statements)
references
References 65 publications
1
145
1
2
Order By: Relevance
“…Many of them are a result of migration of medical devices such as metallic clips after laparoscopic cholecystectomy 1,2 , embolization coil 1 , surgical silk suture 3 , fragmented plastic stent 4 and fractured guidewire 5 . These materials sometimes cause biliary colic 3 and bile duct obstruction 1 or predispose to biliary stone formation 2 , hence they should be removed. Usually, the less-invasive endoscopic method is preferred to remove the foreign bodies 1,3,4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of them are a result of migration of medical devices such as metallic clips after laparoscopic cholecystectomy 1,2 , embolization coil 1 , surgical silk suture 3 , fragmented plastic stent 4 and fractured guidewire 5 . These materials sometimes cause biliary colic 3 and bile duct obstruction 1 or predispose to biliary stone formation 2 , hence they should be removed. Usually, the less-invasive endoscopic method is preferred to remove the foreign bodies 1,3,4 .…”
Section: Discussionmentioning
confidence: 99%
“…These materials sometimes cause biliary colic 3 and bile duct obstruction 1 or predispose to biliary stone formation 2 , hence they should be removed. Usually, the less-invasive endoscopic method is preferred to remove the foreign bodies 1,3,4 . Percutaneous 1,5 or surgical intervention may be necessary if endoscopy failed 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent literature review identified 80 reported cases (of which 69 were analyzed) of either clip migration or clip related stones [2]. The median time to recognition was 2 years after surgery and a majority of cases were managed successfully with ERCP [2].…”
mentioning
confidence: 99%
“…The median time to recognition was 2 years after surgery and a majority of cases were managed successfully with ERCP [2]. Interestingly, 29% of these reports were associated with bile duct strictures, implying that bile duct injuries are probably associated with such cases.…”
mentioning
confidence: 99%